The Influence of the Inquiry Method on Critical Thinking Skills in Learning to Write Explanatory Texts for Grade XI Students at Senior High School - Nur Aisyah; Andi Sahtiani Jahrir; Sultan (Universitas Islam Negeri Palopo, 2025)
This study aims to describe students' ability to write explanatory texts before using the inquiry method, describe students' ability to write explanatory texts after using the inquiry method, and test the effect of applying the inquiry method on the ability to write explanatory texts of eleventh-grade students at SMAN 19 Gowa. This research uses a quantitative research method. Data collection techniques were carried out using essay tests, and the data were analyzed using descriptive and inferential statistics (SPSS 29.0.10). The results of this study show an improvement in students' critical and creative thinking skills in writing explanatory texts after using the inquiry-based learning method. The analysis of the pretest and posttest results shows that before the inquiry method was applied, the majority of students were in the fair and very good categories, with some students in the poor and good categories. After implementation, the majority of students moved to the good and very good categories, showing a significant improvement in their abilities. This improvement is evident in the distribution of student scores, where the average score increased from 58.23 in the pretest to 77.30 in the posttest. Statistical tests using the Paired Sample T-Test showed a t-value of 7.018 with a significance level (p-value < 0.001). Since the p-value is less than 0.05, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. This indicates a significant difference between the pretest and posttest scores, supporting the hypothesis that the inquiry method has a meaningful impact on students' critical and creative thinking abilities. Thus, this research proves that the application of the inquiry method is effective in improving students' abilities in writing explanatory texts, both in terms of quality and variation in critical and creative thinking skills.